Values of literature - Meretoja, Hanna (Value inquiry book series. Philosophy, literature, and politics, 2015)
Why we read literature and why we should read literature are age-old questions that have, in recent years, gained unprecedented scope and intensity, against the backdrop of what has been perceived as a world-wide crisis in the humanities. While scholars frequently discuss different types of value separately, in this volume values of literature are approached in the plural: we argue that the ethical, aesthetic, cognitive, affective, social, historical, and existential values of literature should be explored in connection with each other. The three parts of the book explore the relationship between ethics and aesthetics; the cognitive, affective, and social values of literature; and the construction and questioning of literary values in society. Throughout the book, we discuss the different things literature can do, ranging from affirmation of social dogmas to its capacities for self-questioning and challenging of moral certainties, through the dynamic interplay of its ethical and aesthetic, cognitive and affective aspects.